Dampak Putus Sekolah terhadap Pernikahan Dini di Desa Potil Pololoba Kecamatan Banggai Kabupaten Banggai Laut Provinsi Sulawesi Tengah - Ida Sukmawati Fuadi; Tety Ripursari (Journal of Health Science Community, 2022)
One of the problems related to the health reproductive in adolescents that needs special attention is the incidence of marriage at a young age (less than 19 years old). The coomon reason by marrying early, mothers will still be healthy and active at work when their children grow up and to prevent premarital pregnancy. The study aimed to determine the impact of dropping out of school on early marriage in Potil Pololoba Village, Banggai District, Banggai Laut Regency, Central Sulawesi Province. The study is a correlational study with cross sectional approach. Respondents were taken by total sampling technique. The number of samples is 30 people. The independent variable is dropping out of school and the dependent variable is early marriage. The results were analyzed using the chi square statistical test. The results showed that almost all of the respondents were known to drop out of school as many as 25 (83%) respondents in the category occurred. Early Marriage is known that most of the respondents as many as 21 (70%) in the category occurs. Data analysis show that the significance level is 0.000 ≤ 0.05 therefore H0 is rejected and H1 is accepted, thus there is an impact of dropouts on early marriage. It is recommended that health workers always provide health education to the community, especially in schools about the impact of early marriage which results in maternal and fetal death.